2. Perbedaan Pengaruh Motivasi Terhadap Kinerja Karyawan Berlatar Belakang Kedirgantaraan Dan Non Kedirgantaraan - Indryana Mandraeny (Jurnal Manajemen Dirgantara, 2019)
In running managerial effort toward Sekolah Tinggi Teknologi Kedirgantaraan (STTKD) Yogyakarta, motivation achieved from admission selection of prospective employee is considered important because it can determine the performance of the candidate in the three-month orientation period set by the institution. With the existence of two employee backgrounds needed by STTKD namely aerospace and non-aerospace, this study aims to determine differences in the influence of motivation on the performance of employees with aerospace and non-aerospace backgrounds. Using secondary data in the form of the value of each motivation on the entrance selection and the orientation period performance obtained from the STTKD personnel section, this study was analyzed using regression analysis to obtain the influence values in both groups of employees. The independent variable is motivation and the dependent variable is performance. Respondents were all STTKD employees in 2014 totaling 33 people (10 people from aerospace backgrounds and 23 people from non-aerospace backgrounds). The results of the analysis show there are differences in the effect of motivation on employee performance, with greater value for employees with aerospace background (60%), while for employees with non-aerospace background only 25%.